Police Special Operations in Rio de Janeiro (2006-2020) - Veloso Hirata, Daniel; Christoph Grillo, Carolina; Dirk, Renato (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2021)
This paper addresses the initiative of Grupo de Estudos dos Novos Ilegalismos from Fluminense Federal University, Brazil, of producing a database on police special operations in Rio de Janeiro favelas, to fulfill the gaps left by official statistics and to intervene in public debate and decisions in regard to police use of lethal force in favelas. Based on the perspective of data activism, researchers from GENI/UFF have associated with partner groups to intrude in public space through the display of numbers. Official data available attests the outrageous amount of deaths due to police action, but they do not have any information on police special operations. This paper presents the main results of the research conducted by GENI/UFF on these operations and accounts for the recent experiences of collaboration with other collectives, through the writing of reports, to interfere in a Supreme Court process that addresses police special operations in favelas.